[35S]-t-butylbicyclophosphorothionate binding sites are constituents of the gamma-aminobutyric acid benzodiazepine receptor complex - Supavilai, P (J Neurosci, 1984)
t- Butylbicyclophosphorothionate ( TBPS ), a derivative of potent GABA antagonistic cage convulsants, has recently been introduced ( Squires , R. F., J.E. Casida , M. Richardson, and E. Saederup (1983) Mol. Pharmacol. 13:326–336) as ligand for a GABA-A receptor-linked drug receptor. Using conventionally prepared washed membrane fractions from rat cerebral cortex, we have confirmed that in the presence of 200 mM NaBr [35S] TBPS binds to a high affinity population of binding sites (Kd 26 +/- 5 nM) and that muscimol inhibits [35S] TBPS binding (IC50 0.32 microM) allosterically. In 200 mM NaCl the apparent affinity of [35S] TBPS binding sites is lower (Kd 60 +/- 5 nM), and muscimol has biphasic effects with stimulation at low concentrations of muscimol (EC50 0.023 microM) followed by inhibition at high concentrations (IC50 0.72 microM). Both base line [35S] TBPS binding (in 200 mM NaCl) and muscimol inhibition of [35S] TBPS binding (in 200 mM NaBr) are bidirectionally modulated by the occupancy of benzodiazepine receptors with its ligands. Benzodiazepine receptor agonists, regardless of their structure, enhance and inverse benzodiazepine receptor agonists inhibit base line [35S] TBPS binding and muscimol inhibition of [35S] TBPS binding. Fourteen ligands for benzodiazepine receptors display a similar in vitro profile as benzodiazepine receptor agonists or inverse benzodiazepine receptor agonists on [35S] TBPS binding as their anti- or proconvulsive effects in vivo suggest (Jensen, L. H., E. N. Petersen, and C. Braestrup (1983) Life Sci. 33: 393–399). That [35S] TBPS binding sites are constituents of a GABA benzodiazepine receptor complex is also suggested by a number of membrane pretreatments.(ABSTRACT TRUNCATED AT 250 WORDS)